Experimentação-com-Geogebra: revisitando alguns conceitos da análise real - Mazzi, Lucas Carato [UNESP] (2014)
The aim of this research is to identify the possibilities and the limitations of the software GeoGebra, in an experimentation process of some fundamental concepts of Mathematical Analysis, as convergent sequences, bounded sequences and monotone sequences, besides investigating the Intermediate Value Theorem. This work is supported by the theoretical construct Humans-with-Media. This epistemological conception emphasizes the role of media in the process of producing knowledge and argues that it is produced by a collective Humanswith- Media. This inquiry has a qualitative approach since the concern is the deep understanding of a particular social group, in this case, Student-with-GeoGebra. In order to achieve the goal, I used Teaching Experiments, which are exploratory tools and aim to investigate the student's mathematics. The elements that constitute the Teaching Experiments are: a sequence of teaching episodes with a teaching agent, one or more students; witnesses and a recording method. In this particular case, the teaching experiments were performed with two pairs of students enrolled in the undergraduate program in mathematics at UNESP - Rio Claro. The survey results indicate that the software helped the students draw up conjectures, test them and, when appropriate, refute them. The experimentation-with-technology proved to be important for the conviction and for understanding some mathematical ideas discussed throughout the work, and provide a change in the communication style of the students